Attention in schizophrenia and in epileptic psychosis - Kairalla,I.C.J (2008)
The adaptive behavior of human beings is usually supported by rapid monitoring of outstanding events in the environment. Some investigators have suggested that a primary attention deficit might trigger symptoms of schizophrenia. In addition, researchers have long discussed the relationship between schizophrenia and the schizophrenia-like psychosis of epilepsy (SLPE). On the basis of these considerations, the objective of the present study was to investigate attention performance of patients with both disorders. Patient age was 18 to 60 years, and all patients had received formal schooling for at least four years. Patients were excluded if they had any systemic disease with neurologic or psychiatric comorbidity, or a history of brain surgery. The computer-assisted TAVIS-2R test was applied to all patients and to a control group to evaluate and discriminate between selective, alternating and sustained attention. The TAVIS-2R test is divided into three parts: one for selective attention (5 min), the second for alternating attention (5 min), and the third for the evaluation of vigilance or sustained attention (10 min). The same computer software was used for statistical analysis of reaction time, omission errors, and commission errors. The sample consisted of 36 patients with schizophrenia, 28 with interictal SLPE, and 47 healthy controls. The results of the selective attention tests for both patient groups were significantly lower than that for controls. The patients with schizophrenia and SLPE performed differently in the alternating and sustained attention tests: patients with SLPE had alternating attention deficits, whereas patients with schizophrenia showed deficits in sustained attention. These quantitative results confirmed the qualitative clinical observations for both patient groups, that is, that patients with schizophrenia had difficulties in focusing attention, whereas those with epilepsy showed perseveration in attention focus.